The Azerbaijani Factor in the Clash of the Iranian and Turkish ‘Crescents’: A ‘Geopolitical New Moon’ in the South Caucasus - Mirmehdi M. Aghazada (Vestnik RUDN. International Relations)
The Islamic Republic of Iran and the Republic of Türkiye, two historical rivals in the South Caucasus and the Middle East, pay special attention to relations with the Republic of Azerbaijan. This is primarily due to ethnolinguistic, religious-ideological, and geopolitical factors. The aim of the paper is to identify the distinctive characteristics of the Iranian and Turkish crescents, as well as Azerbaijan’s place in the clash of these two foreign policy strategies. The Iranian crescent refers to Iran’s influence and/or presence in Lebanon, Syria, Iraq, Azerbaijan, Bahrain, and Yemen. The author introduces the term ‘Turkish crescent’ as Türkiye’s foreign policy strategy, the main aim of which is to strengthen the country’s position in the South Caucasus and the Middle East by building up military forces and expanding trade and economic ties, as well as to contain Iranian influence in the region. The Turkish crescent means Türkiye’s influence and/or presence in Libya, Cyprus, Syria, Iraq, Azerbaijan, Qatar, and Somalia. The term ‘geopolitical new moon’ refers to the new geopolitical realities that emerged after the Second Karabakh War in the South Caucasus and have an impact on the regional security architecture, including the policies of Iran and Türkiye in this region. The article analyzes the peculiarities of the Iranian and Turkish crescents and the use of the Azerbaijani factor by Iran and Türkiye in implementing their strategies against each other. This paper is based on constructive realism, as religious, ideological, and ethnic factors play a special role in the rivalry between Iran and Türkiye in the South Caucasus and the Middle East, along with military, political, and economic factors. The author employs a descriptive-analytical approach, gathering necessary information from documents, scientific papers, media materials, and comparative analysis to assess the impact of the rivalry between Türkiye and Iran on Azerbaijan’s foreign policy orientation. It can be concluded that Iran lost to Türkiye in the Azerbaijani segment of the clash of two ‘crescents.’